Синтез, фізико-хімічні та біологічні властивості 8-R-тіопохідних 1-бензилтеоброміну - Іванченко, Дмитро Григорович; Романенко, Микола Іванович; Самура, Б. А.; Корнієнко, В. І.; Иванченко, Д. Г.; Романенко, Н. И.; Корниенко, В. И.; Ivanchenko, D. G.; Romanenko, M. I.; Samura, B. A.; Kornienko, V. I. (My University, 2015)
Основним шляхом створення нових лікарських препаратів є структурна модифікація відомих природних сполук, які мають високу біологічну активність. У цьому аспекті увагу дослідників привертають похідні ксантину, які є антагоністами аденозинових рецепторів, інгібіторами фосфодіестерази та індукторами гістондезацетилази. Це сприяло широкому їх застосуванню в медицині (амінофілін, вентакс, нео-теофедрин, апо-окстрифілін та ін.) при лікуванні астми, бронхіту і хронічної обструктивної хвороби легень. Також похідні ксантину знайшли застосування як діуретики, аналгетики, серцеві стимулятори, протизапальні, психотропні й ниркові захисні агенти. Раніше нами встановлено, що похідні теоброміну виявляють діуретичну, протизапальну, антиоксидантну дію. Метою роботи є розроблення оригінальних методів синтезу неописаних в літературі 8-тіопохідних 1-бензилтеоброміну – потенційних біоактивних сполук, вивчення їхніх фізико-хімічних та біологічних властивостей. Основным путем создания новых лекарственных препаратов является структурная модификация известных природных соединений, обладающих высокой биологической активностью. В этом аспекте внимание исследователей привлекают производные ксантина, которые являются антагонистами аденозиновых рецепторов, ингибиторами фосфодиэстеразы и индукторами гистондезацетилазы. Это способствовало широкому их применению в медицине при лечении астмы, бронхита и хронической обструктивной болезни легких. Также производные ксантина нашли применение в качестве диуретиков, анальгетиков, сердечных стимуляторов, противовоспалительных, психотропных и почечных защитных агентов. Целью работы является разработка оригинальных методов синтеза неописанных в литературе 8-тиопроизводных 1-бензилтеобромина и изучение их физико-химических и биологических свойств. Острая токсичность синтезированных соединений была изучена методом Кербера. Изучение диуретического действия полученных соединений проводили по методу Берхина. Анальгетическое действие синтезированных ксантинов изучено на модели «уксусных корчей», противовоспалительное – на модели острого асептического отека. Антиоксидантную активность изучали in vitro методом неферментного инициирования свободнорадикального окисления. Key way for creating new medicinal drugs is structural modification of known and existent natural compounds with high biological activity. In this aspect researchers’ attention is drawn by xanthine derivatives which appear to be antagonists of adenosine receptors, phosphodiesterase inhibitors and histone deacetylase inducers. This resulted in their widespread application in medicine to cure asthma, bronchitis and chronic obstructive pulmonary disease. In addition, xanthine derivatives are used as diuretics, analgesics, heart pacemakers, anti-inflammatory, psychotropic and renal protective agents. The aim of this work lies in developing unique methods to synthesize undocumented in other scientific papers 8-thioderivatives of 1-benzylthiobromine and also studying of their physical, chemical and biological properties. Acute toxicity of synthesized compounds has been studied with the application of Kerber method. The study of diuretic activity of obtained compounds was carried out applying Berkhin method. Analgesic activity of synthesized xanthines was studied at ‘acetic acid writhing’ model. Anti-inflammatory activity was studied at ‘acute aseptic edema’ model. Antioxidant activity was studied in vitro using the method of non-enzymatic initiation of free-radical oxidation. Heating of 1-benzyl-8-bromotheobromine with double excess of sodium sulphidenonahydrate in dimethylformamide environment results in formation of 8-thiotheobromine. Reactions of thioxanthines with halogenketones and chloroacetamide proceed smoothly with their short-time heating in aqueous alcohol environment. By applying such computer programs as ALOGPS, DRAGON, GUSAR and ACD /Percepta Platform was established viability of further invitro and invivo research.
Синтез, физико-химические и биологические свойства 8-R-тиопроизводных 1-бензилтеобромина
Synthesis, physical-chemical and biological properties of 8-R-thioderivatives of 1-benzyltheobromine
Keywords: синтез; теобромін; 8-тіопохідні; ПМР-спектроскопія; гостра токсичність; біологічна дія; теобромин; 8-тиопроизводные; ПМР-спектроскопия; острая токсичность; биологическое действие; synthesis; theobromine; 8-thioderivatives; NMR-spectroscopy; acute toxicity; biological action